2014
DOI: 10.1016/j.bbmt.2013.11.032
|View full text |Cite
|
Sign up to set email alerts
|

Does Total Body Irradiation Conditioning Improve Outcomes of Myeloablative Human Leukocyte Antigen–Identical Sibling Transplantations for Chronic Lymphocytic Leukemia?

Abstract: An allogeneic hematopoietic cell transplant (HCT) from an HLA-identical donor after high-dose (myeloablative) pre-transplant conditioning, is an effective therapy for some people with chronic lymphocytic leukemia (CLL). Because CLL is a highly radiosensitive cancer, we hypothesized total body irradiation (TBI) conditioning regimens may be associated with better outcomes than those without TBI. To answer this we analyzed data from 180 subjects with CLL receiving myeloablative doses of TBI (N=126) or not (N=54),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…From the recently reported MA experience comparing chemotherapy- vs. TBI-based conditioning, which included the MA cohort of patients from the current study, there were no differences in TRM, relapse, PFS or survival [31]. Investigation of novel treatment agents for conditioning as well as adoptive cellular therapy studies and post-transplant maintenance therapy may be further explored.…”
Section: Discussionmentioning
confidence: 92%
“…From the recently reported MA experience comparing chemotherapy- vs. TBI-based conditioning, which included the MA cohort of patients from the current study, there were no differences in TRM, relapse, PFS or survival [31]. Investigation of novel treatment agents for conditioning as well as adoptive cellular therapy studies and post-transplant maintenance therapy may be further explored.…”
Section: Discussionmentioning
confidence: 92%
“…The 5-year EFS of 35% in this large study fits right in the middle of the reported range between 28 and 43% reported from smaller series of patients. [6][7][8]18,19 When counting from the day of allo-HCT, 28% of patients (95% CI, 25-31) maintained disease control at 10 years. For patients who passed the 2-and 5-year landmark event-free, the fraction of patients who maintained disease control at 10 years from allo-HCT increased to 56% (95% CI, 51-62) and 79% (95% CI, 73-85).…”
Section: Discussionmentioning
confidence: 99%
“…In patients who passed the 2year landmark event-free, relapse/progression and NRM continued to occur. The cumulative incidence of relapse at 8 years after the landmark was 24% (95% CI, [20][21][22][23][24][25][26][27][28] and NRM was 20% (95% CI, [16][17][18][19][20][21][22][23][24]. The probability of being alive 10 years after allo-HCT (8 years after the landmark) was 65% (95% CI, 60-70).…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…In previous literatures, TRM was generally defined as death from any cause without leukemia relapse [ 15 , 16 ]. Many cases of death after HSCT are due to infectious causes [ 17 ], and the risk of opportunistic infection is small after 3 months [ 18 ]. For this reason, we limited the definition of TRM to 3 months after TBI followed by HSCT.…”
Section: Methodsmentioning
confidence: 99%